Dentin Sialophosphoprotein–derived Proteins in the Dental Pulp. (August 2015) - Yamamoto, R.; Oida, S.; Yamakoshi, Y.
Porcine dentin sialophosphoprotein (DSPP), the most abundant noncollagenous protein in dentin, is critical for proper mineralization of tooth dentin. DSPP is processed by proteases into 3 major domains: dentin sialoprotein (DSP), dentin glycoprotein (DGP), and dentin phosphoprotein (DPP). There are at least 2 mRNA variants expressed from the Dspp gene: one encodes the full-length DSPP protein (DSP+DGP+DPP); the other encodes only DSP. The shorter transcript is generated through the use of a polyadenylation signal within intron 4, immediately following the DSP coding region (DGP and DPP are encoded by exon 5). We fractionated DSPP-derived proteins from the dental pulp of developing porcine incisors using heparin chromatography. DSP was identified, but little DPP could be detected in any fractions. BMP-1 digestion of DSPP-derived proteins extracted from dental pulp did not generate new DPP bands on sodium dodecyl sulfate–polyacrylamide gel electrophoresis (indicating an absence of intact DSPP), although the results suggested another BMP-1 cleavage site within DSP. We further purified DSPP-derived protein by reversed-phase high-performance liquid chromatography. Its amino acid composition was similar to DSP. Expression of the full-length Dspp mRNA by quantitative real-time polymerase chain reaction analysis was significantly higher in odontoblasts than in pulp, while expression of the DSP-only mRNA was almost equal in odontoblasts and in the body of the pulp. Expression of the full-length Dspp mRNA was also significantly higher than the expression of DSP-only mRNA in odontoblasts. Both the full-length and the DSP-only Dspp mRNA showed only trace expression in the pulp tip. We conclude that use of the 3′ polyadenylation signal in exon 5 predominates in fully differentiated odontoblasts, while both polyadenylation signals are used throughout odontoblast differentiation.